ANALISIS KEBIJAKAN PENGELOLAAN PROGRAM STUDI PENDIDIKAN JASMANI FKIP UMS (Studi Periode Kepemimpinan Tahun 2017-2021 dan 2021-2025) - Dewantoro, ridho astri; Anugrah Nur Warthadi; Nur Subekti; Gatot Jariono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The transformation of study program management policies in higher education is a key factor in improving academic quality and student achievement. This study aims to analyze the effectiveness of the management policies of the Physical Education Study Program of the Faculty of Teacher Training and Education, University of Muhammadiyah Yogyakarta (FKIP UMS) in improving the academic and non-academic quality of students. The study used a qualitative descriptive approach with students and alumni from across the 2017–2025 cohort as subjects. Data collection techniques were carried out through in-depth interviews, observation, and documentation to obtain a comprehensive picture of the implementation of study program policies. Data analysis was carried out through the stages of systematic reduction, presentation, and conclusion drawing. The results of the study indicate that policies based on internal quality assurance and the Outcome-Based Education curriculum are able to improve the quality of academic governance and the relevance of graduates to the needs of the workforce. The achievement of superior accreditation is an indicator of the success of consistent and sustainable academic policy implementation. The findings also indicate that academic flexibility policies and institutional support contribute to improving student non-academic achievement. The success of Tito Hendra Septa Kurnia Wijaya in winning a gold medal at the 2025 SEA Games is concrete evidence of the effectiveness of student athlete development policies. The dynamics of policies between leadership periods demonstrate continuity and innovation in study program management. The 2017–2021 period focused on strengthening governance and quality assurance, while the 2021–2025 period emphasized innovation, internationalization, and enhancing student achievement. This study concluded that adaptive, quality-based study program management policies can create a competitive educational ecosystem and produce graduates who excel academically and non-academically.